Measuring Antibiotic Appropriateness for Urinary Tract Infections in Nursing Home Residents. (31st May 2017) - Eure, Taniece; LaPlace, Lisa L.; Melchreit, Richard; Maloney, Meghan; Lynfield, Ruth; Whitten, Tory; Warnke, Linn; Dumyati, Ghinwa; Quinlan, Gail; Concannon, Cathleen; Thompson, Deborah; Stone, Nimalie D.; et al.
Abstract : We assessed the appropriateness of initiating antibiotics in 49 nursing home (NH) residents receiving antibiotics for urinary tract infection (UTI) using 3 published algorithms. Overall, 16 residents (32%) received prophylaxis, and among the 33 receiving treatment, the percentage of appropriate use ranged from 15% to 45%. Opportunities exist for improving UTI antibiotic prescribing in NH. Infect Control Hosp Epidemiol 2017;38:998–1001